Capsular polysaccharide from a fish-gut bacterium induces/promotes apoptosis of colon cancer cells in vitro through Caspases' pathway activation. (15th February 2022) - Di Guida, Rossella; Casillo, Angela; Stellavato, Antonietta; Kawai, Soichiro; Ogawa, Takuya; Di Meo, Celeste; Kawamoto, Jun; Kurihara, Tatsuo; Schiraldi, Chiara; Corsaro, Maria Michela
Abstract: Among the widespread malignancies colorectal cancer is the most lethal. Treatments of this malignant tumor include surgery for lesions and metastases, radiotherapy, immunotherapy, and chemotherapy. Nevertheless, novel therapies to reduce morbidity and mortality are demanding. Natural products, such as polysaccharides, can be a valuable alternative to sometimes very toxic chemotherapeutical agents, also because they are biocompatible and biodegradable biomaterials. Microbial polysaccharides have been demonstrated to fulfill this requirement. In this paper, the results about the structure and the activity of a capsular polysaccharide isolated from the psychrotroph Pseudoalteromonas nigrifaciens Sq02-Rif r, newly isolated from the fish intestine, have been described. The characterization has been obtained by spectroscopic and chemical methods, and it is supported by the bioinformatic analysis. The polymer activates Caspases 3 and 9 on colon cancer cells CaCo-2 and HCT-116, indicating a promising antitumor effect, and suggesting a potential capacity of CPS to induce apoptosis. Graphical abstract: Unlabelled Image Highlights: CPS was isolated from the cold-adapted bacterium Pseudoalteromonas nigrifaciens Sq02. The primary structure of the repeating unit was established by chemical and NMR analyses. The CPS biosynthesis pathway was hypothesized by bioinformatic analysis. The polysaccharide proved a cytotoxic action on colon tumor cells/on HCT-116 in vitro.